PELATIHAN KETERAMPILAN PEMULASARAAN JENAZAH BAGI KELUARGA DI DESA BOJONGGALING KECAMATAN BOJONGGENTENG KABUPATEN SUKABUMI - Acep Sujana; Muhamad Rafliansyah; Zaenudin Zaenudin (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2022)
One of the important issues related to human relations with other humans is the problem of caring for corpses. Islam pays very serious attention to this issue, so this is one of the obligations that must be fulfilled by mankind. The funeral of the corpse is the process of taking care of the corpse which includes the activities of bathing, shrouding, worshiping and burying the corpse. Immediately repent if you commit a big sin or a small sin. Caring for and organizing corpses for Muslims is fard kifayah. If there is someone or several groups of people who have carried out this obligation, then the obligation of others to carry it out has fallen. Organizing the corpse is the obligation of the closest family of the deceased, if the closest family is not there, then the other Muslims. the management of the corpses. People prefer to ask for help from Ustadz or local teachers to take care of their family's bodies rather than taking care of them themselves. Therefore, it is necessary to empower the community in relation to the care of corpses, so that if one day they are needed they are ready to take care of the bodies of their own families. The purpose of this activity is to provide skills training for the management of corpses in Bojonggaling Village, Bojonggenteng District, Sukabumi Regency. It is hoped that this training can maximize the role of humanist and religious values for the benefit of the community.